Electrode-embedding member, its manufacturing method, and substrate holding member
By using a combination of Mo carbide electrode and W metal connector, the problem of unstable electrode resistance value is solved, the reliability of the electrode and the uniformity of the temperature distribution are achieved, the freedom of the electrode design is improved and the cost is reduced.
Patent Information
- Application Number
- JP2020209029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-17
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2040-12-17
AI Technical Summary
The prior art is difficult to increase the resistance value of the electrode while maintaining the reliability of the electrode, resulting in uneven temperature distribution of the electrode in semiconductor manufacturing equipment, and it is easy to react with the ceramic material when using Mo as the electrode material, resulting in a change in resistance.
Mo carbide is used as the electrode material, and the volume resistivity of the electrode is increased by C coating and appropriate heat treatment process to form a Mo carbide electrode, combined with a W metal connector to improve the reliability and design freedom of the electrode.
The stability and uniformity of the electrode resistance value are achieved, the temperature distribution changes of the electrode during use are reduced, the reliability and design flexibility of the electrode are improved, and the manufacturing cost is reduced.
Smart Images

Figure 0007628358000001 
Figure 0007628358000002 
Figure 0007628358000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode-embedded member, a manufacturing method thereof, and a substrate holding member. [Background technology]
[0002] 2. Description of the Related Art Hitherto, there have been proposed, as members for semiconductor manufacturing equipment, members with embedded electrodes, such as susceptors having electrodes embedded in a ceramic sintered body, electrostatic chucks, or ceramic heaters.
[0003] Patent Document 1 discloses a ceramic heater technology that has a ceramic substrate and a resistance heating element embedded in the substrate, the resistance heating element having a main body made of a high melting point metal and a coating film that coats the main body, the thermal expansion coefficient of the coating film being greater than the thermal expansion coefficient of the main body, and the thickness of the coating film being 2 μm or more, for the purpose of preventing the resistance value of the resistance heating element from increasing or the resistance heating element from breaking when the ceramic heater is repeatedly subjected to heating-cooling cycles and used for a long period of time. Patent Document 1 also describes that the coating film is preferably formed of a material selected from the group consisting of TiN, Mo2C, NbC, TiC, VC, ZrC, WC, TaC, TaN, and ZrN, the high melting point metal is tungsten, and particularly preferably the coating film is formed of TiN.
[0004] Patent Document 2 aims to provide a silicon nitride member and a manufacturing method thereof that can improve resistance changes during repeated heating and cooling tests and obtain a highly reliable ceramic heater, and discloses a silicon nitride member in which a high-melting point metal such as tungsten or molybdenum is embedded in a member whose main component is silicon nitride, and the high-melting point metal is coated with a high-melting point metal carbide, and a manufacturing method for a silicon nitride member in which a carbon-containing high-melting point metal such as tungsten or molybdenum is embedded in a silicon nitride molded body, which is then fired, and at least a high-melting point metal carbide is generated on the surface of the high-melting point metal during the firing.
[0005] Patent Document 3 discloses a technology for a manufacturing method of a ceramic heater, for the purpose of providing a ceramic heater in which the variation in resistance value of the heater electrode layer within a substrate is small and which can uniformly heat a semiconductor wafer, is used to form a heater electrode layer on an aluminum nitride green sheet, and then a heat treatment process is carried out on the green sheet, in which the green sheet is heated in an inert gas atmosphere at a temperature range lower than the formation temperature of ditungsten carbide, and then a main firing process is carried out to completely sinter the green sheet, thereby completing ceramic heater 1. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 07-135068 [Patent Document 2] Japanese Patent Application Publication No. 04-087181 [Patent Document 3] JP 2000-12194 A Summary of the Invention [Problem to be solved by the invention]
[0007] When embedding a mesh electrode in a ceramic sintered body, it may be difficult to set the resistance of the electrode high depending on the shape of the mesh. This is due to the fact that the volume resistivity of the metal itself is essentially low. However, there are cases where the resistance value of the electrode is required to be high due to the specifications of the power source and other restrictions on use. In such cases, it is necessary to narrow the cutting width of the mesh and lengthen it in the longitudinal direction, but there is a limit to narrowing the cutting width because the number of wires within the cutting width directly affects the variation in the resistance value and reduces the reliability of the electrode. For example, when the electrode-embedded member is used as a heater, if the cutting width is made too narrow, the temperature distribution within the substrate surface will vary, so it is not possible to obtain a reliable electrode with sufficient resistance and uniform temperature distribution within the substrate surface by simply narrowing the cutting width.
[0008] In addition, when Mo is used as a mesh electrode, it is necessary to embed the Mo mesh electrode in a ceramic molded body and sinter it, but it reacts with the binder of the ceramic raw material, the carbon jig, and the C component mixed in from the environment. Therefore, the reactivity varies depending on the manufacturing conditions and the position of the electrode, which leads to variation in the degree of carbonization of Mo, and the resistance value of the Mo electrode varies within the substrate surface, which results in variation in the temperature distribution within the substrate surface. This is because Mo has a small volume resistivity, but the volume resistivity of carbonized Mo2C is large, and this effect becomes significant. In addition, although it is possible to embed carbide Mo2C in advance to increase the volume resistivity, Mo2C is brittle and has low strength and ductility, so it is not practical to weave Mo2C into a mesh.
[0009] Therefore, there has been a demand for an electrode embedding material that, when the Mo mesh electrode is embedded in a ceramic molded body and sintered, promotes carbonization of the Mo mesh electrode to carbonize the entire electrode, thereby increasing the resistance value of the heater electrode and suppressing variations in the temperature distribution within the base surface.
[0010] However, since Patent Document 1 aims to prevent the resistance heating element from increasing in resistance value or breaking when the ceramic heater is used for a long period of time by repeatedly subjecting it to heating-cooling cycles, it is unable to sufficiently carbonize the Mo mesh electrode, whereas Patent Document 2 aims to improve the change in resistance during repeated temperature rise and fall tests, it is unable to sufficiently carbonize the Mo mesh electrode.
[0011] Patent Document 3 aims to provide a ceramic heater that has small variation in the resistance value of the heater electrode layer within a substrate and can uniformly heat a semiconductor wafer. However, the technology uses a conductive paste containing tungsten monocarbide particles to prevent the generation of ditungsten monocarbide, and when this technology is applied to a Mo mesh electrode, it is not possible to sufficiently carbonize the Mo mesh electrode.
[0012] The inventors discovered that a Mo mesh electrode can be sufficiently carbonized by coating it with C and subjecting it to heat treatment at an appropriate temperature, in addition to the binder of the ceramic raw materials, the C components mixed in from the carbon jig and the environment, and thus completed the present invention.
[0013] In other words, the present invention has been made in consideration of the above circumstances, and aims to provide an electrode-embedded member, a manufacturing method thereof, and a substrate holding member that can increase the resistance of an electrode even with a design that does not impair the reliability of the electrode, increase the degree of freedom in electrode design, and suppress variation in the resistance value of the electrode within the substrate surface. [Means for solving the problem]
[0014] (1) In order to achieve the above object, the present invention provides an electrode-embedding member, which comprises a flat-plate-shaped substrate made of a ceramic sintered body, and an electrode formed of a mesh woven with wires and embedded in the substrate, the electrode being made of a bulk body of Mo carbide. The electrode is electrically connected to the connection member, and the connection member includes a W metal embedded in the substrate. The connection member has a W carbide layer on a surface thereof. It is characterized by the fact that
[0015] In this way, by constructing the electrodes from bulk Mo carbide (Mo2C), the volume resistivity becomes high, so the resistance of the electrodes can be increased without compromising the reliability of the electrodes, and the degree of freedom in electrode design can be increased. Also, the variation in the resistance value of the electrodes within the surface can be suppressed.
[0016] (2) As mentioned above The electrode-embedded member of the present invention further comprises a connection member electrically connected to the electrode and containing W metal embedded in the base, the connection member having a W carbide layer on its surface.
[0017] In this way, by constructing the connection member electrically connected to the electrode from a material containing W metal and having a W carbide layer on the surface, it is possible to prevent the connection member from becoming highly resistant, improve the reliability of the electrical connection with the connection member, and also to prevent the connection member from becoming embrittled, thereby reducing the risk of cracks occurring in the connection member.
[0018] (3) In the electrode-embedding member of the present invention, the wire forming the mesh of the electrode has a wire diameter of 0.02 mm or more and 0.15 mm or less.
[0019] This makes it easier to design the electrodes to have a high resistance, allowing greater freedom in electrode design, and also allows the heat treatment time to be relatively short, reducing manufacturing costs.
[0020] (4) The substrate holding member of the present invention is characterized by comprising an electrode-embedding member according to any one of (1) to (3) above, and a terminal electrically connected to the electrode.
[0021] This makes it possible to configure a substrate holding member using an electrode-embedded member that allows a high degree of freedom in electrode design and can suppress variations in the resistance value of the electrodes within the surface.
[0022] (5) Furthermore, the present invention provides a method for producing an electrode-embedded member formed of a sintered ceramic body, the method comprising the steps of: forming a plurality of ceramic bodies from a ceramic raw material powder; degreasing the plurality of ceramic bodies at a predetermined temperature or higher for a predetermined time or longer to produce a plurality of ceramic degreased bodies; preparing an electrode formed of a mesh having Mo wires woven therein and coated with carbon; combining the electrode and the plurality of ceramic degreased bodies to form an electrode-embedded member precursor formed in a flat plate shape and having an electrode embedded therein; a heat treatment step of heat treating the electrode-embedded member precursor at a temperature of 800°C to 1500°C for 7 hours or longer; and a firing step of uniaxially pressurizing and firing the electrode-embedded member precursor after the heat treatment in a direction perpendicular to a main surface of the electrode-embedded member precursor to fire the electrode-embedded member.
[0023] This promotes carbonization of the electrode during the heat treatment process, allowing the electrode to be made of a bulk of Mo carbide. As a result, the volume resistivity of the electrode material increases, making it possible to increase the resistance of the electrode without compromising its reliability, and thus increasing the degree of freedom in electrode design. In addition, it is possible to suppress variation in the resistance value of the electrode within the surface. Effect of the Invention
[0024] According to the present invention, since the electrode of the electrode-embedded member is made of a bulk of Mo carbide, the volume resistivity is increased, so that the resistance of the electrode can be increased without impairing the reliability of the electrode, and the degree of freedom in electrode design can be increased. Also, the variation in the resistance value of the electrode in the plane can be suppressed. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a cross-sectional view showing an example of an electrode-embedded member according to the embodiment. [Diagram 2] 11 is a cross-sectional view showing a modified example of an electrode-embedded member according to the embodiment. FIG. [Diagram 3]2 is a cross-sectional view showing an example of a substrate holding member according to an embodiment. FIG. [Figure 4] 11 is a cross-sectional view showing a modified example of the substrate holding member according to the embodiment. FIG. [Diagram 5] 4 is a flowchart showing a method for manufacturing an electrode-embedded member according to the embodiment. [Figure 6] 3(a) to 3(d) are cross-sectional views each showing a schematic diagram of one stage in a manufacturing process for an electrode-embedded member according to an embodiment of the present invention. [Figure 7] 1(a) to 1(c) are cross-sectional views each showing a schematic diagram of one stage in a manufacturing process of a substrate holding member according to an embodiment. [Figure 8] 1 is a table showing the production conditions and measurement results of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Next, an embodiment of the present invention will be described with reference to the drawings. In order to facilitate understanding of the description, the same reference numerals are used for the same components in each drawing, and duplicated descriptions will be omitted. In the configuration diagrams, the size of each component is conceptually shown, and does not necessarily represent the actual dimensional ratio.
[0027] [Embodiment] [Configuration of electrode embedding material] First, the configuration of an electrode-embedded member according to this embodiment will be described. Fig. 1 is a cross-sectional view showing an example of an electrode-embedded member according to an embodiment of the present invention. The electrode-embedded member 100 according to this embodiment includes a base 110 and an electrode 120. The electrode-embedded member 100 is applied to a heater, an electrostatic chuck, etc.
[0028] The base 110 is made of a ceramic sintered body, formed in a flat plate shape, and has a mounting surface 112 on one of its main surfaces for mounting a substrate. Various materials can be used for the material of the base 110 depending on the application. For example, AlN, Al2O3, Si3N4, SiC, etc. can be used. The shape of the base 110 can be various shapes such as a disk shape, a polygonal shape, an ellipse shape, etc.
[0029] The ceramic sintered body forming the base 110 is preferably composed mainly of AlN. The term "composed mainly of AlN" means that the ceramic sintered body contains 90 wt% or more of AlN. In order to increase the thermal conductivity, sintering aids made of oxides of 2a group elements or 3a group elements are often added to AlN ceramics. In general, it is known that the thermal conductivity increases when the amount of sintering aid added is increased, but adding more than a certain amount causes a decrease in the thermal conductivity. Therefore, it is desirable to set the content of the sintering aid made of oxides of 2a group elements or 3a group elements to 10 wt% or less. Examples of additives of 2a group elements include Mg, Ca, Sr, Ba, etc., and examples of additives of 3a group elements include Y, La, Sm, Ce, etc.
[0030] A ceramic sintered body mainly composed of AlN has high thermal conductivity and excellent heat resistance and plasma resistance, and the thermal conductivity can be easily adjusted by adjusting the type and amount of sintering aid added. Therefore, by forming the base 110 from a ceramic sintered body mainly composed of AlN, the thermal conductivity can be adjusted and the base 110 with excellent heat resistance and plasma resistance can be configured.
[0031] The electrode 120 is formed of a mesh in which wires are woven, and is embedded in the base 110. The wires forming the mesh preferably have a wire diameter of 0.02 mm or more and 0.15 mm or less. This makes it easier to design the resistance of the electrode to a high value, and allows for greater freedom in electrode design. In addition, the heat treatment time can be relatively shortened, and manufacturing costs can be reduced. Mo has a high melting point and is difficult to process, so wires with a wire diameter of less than 0.02 mm are difficult to manufacture. In addition, if a mesh is formed by weaving wires with a wire diameter of more than 0.15 mm, it may be difficult to increase the resistance value, making it difficult to design the required resistance value.
[0032] Furthermore, if the wire diameter is greater than 0.15 mm, there is a high risk of the wire cracking during sintering. Also, if the thickness of the mesh at the wire intersection is greater than 0.3 mm, there is an increased risk of the insulation layer cracking when the ceramics on the upper part of the electrode 120 are configured as a thin insulation layer. In this way, by configuring the electrode 120 with sufficiently thin wires, it is possible to further reduce the risk of the wire cracking during sintering, and even if the ceramics on the upper part of the electrode 120 are configured as a thin insulation layer, it is possible to further reduce the risk of the insulation layer cracking.
[0033] The electrode 120 is made of a bulk body of Mo carbide (Mo2C). In this way, by making the electrode 120 of Mo carbide, the volume resistivity can be increased. Furthermore, by making the electrode 120 of a bulk body, the risk of disconnection can be reduced even when the width of the electrode 120 is designed to be narrow, compared to an electrode made by firing a paste of an electrode material, and the reliability of the electrode 120 can be increased. In other words, by making the electrode 120 of a bulk body of Mo carbide, the volume resistivity is high, the reliability is not impaired even when the width of the electrode is narrowed, and the in-plane resistance variation is unlikely to occur, so that the resistance of the electrode 120 can be increased and the degree of freedom in electrode design can be increased.
[0034] The electrode 120 being composed of Mo carbide means that an elemental mapping analysis of the entire cross section of the electrode 120 is performed by EPMA analysis, and C and Mo are quantified in atom % terms by the ZAF method, resulting in a C / (C+Mo) ratio of 0.20 or more.
[0035] The electrode 120 being made of a bulk body means that the porosity of the electrode 120 is 5% or less. The porosity of the electrode 120 can be measured, for example, by photographing a cross section of the electrode 120 with a scanning electron microscope (SEM) at a magnification of 1000 to 5000 times, and binarizing a 30 μm × 30 μm field of view from the photographed data using free software "ImageJ" developed by the National Institutes of Health (NIH). Note that five fields of view may be observed at random as measurement points.
[0036] The substrate 110 may include a plurality of electrodes. For example, by including a heater electrode and an electrostatic attraction electrode, the electrode-embedded member 100 can be used as a heater-equipped electrostatic chuck. In this case, at least one of the electrodes may be the electrode 120 of the present invention. Two or more electrodes may be the electrode 120 of the present invention.
[0037] The electrode-embedding member 100 may further include a connection member 130. FIG. 2 is a cross-sectional view showing a modified example of the electrode-embedding member according to the embodiment. The connection member 130 is embedded in the base 110 and electrically connected to the electrode 120. This allows electricity to be supplied to the electrode 120 via the connection member 130, and allows stable supply of electricity. The connection member 130 preferably contains W metal. The connection member 130 contains W metal when this is confirmed by detecting 0.9 or more W in a cross section of the connection member 130 in a quantitative analysis by the ZAF method of EPMA analysis.
[0038] The thickness of the connection member 130 is preferably 0.2 mm or more and 5 mm or less. If it is less than 0.2 mm, there is an increased risk of breakage when forming the terminal hole 142 for connecting the terminal 140. If it is more than 5 mm, there is an increased risk of cracks occurring in the base 110 due to the difference in contraction rate between the base 110 and the ceramics of the base 110 during firing and the difference in thermal expansion rate during use.
[0039] The connection member 130 may have a W carbide layer on the surface. In this case, the W carbide layer is preferably greater than 0 μm and less than 20 μm. In this way, by configuring the connection member 130 to have a W carbide layer on the surface and making the thickness very thin, it is possible to suppress the connection member 130 from becoming highly resistant, and the reliability of the electrical connection via the connection member 130 can be further improved, and the embrittlement of the connection member 130 can be suppressed, and the risk of cracks occurring in the connection member 130 can be reduced. In the manufacturing method of the present invention, the carbonization of W is less likely to progress because the heat treatment temperature is relatively lower than the temperature at which the carbonization of W progresses, and even when the connection member 130 made of W is embedded, the W carbide layer on the surface can be made thin.
[0040] The electrode embedding member of the present invention has a high volume resistivity due to the electrode being made of a bulk of Mo carbide, so that the resistance of the electrode can be increased even with a design that does not impair the reliability of the electrode, thereby increasing the degree of freedom in electrode design and suppressing the variation in the resistance value of the electrode within the plane.
[0041] [Configuration of the substrate holding member] FIG. 3 is a cross-sectional view showing an example of a substrate holding member according to an embodiment of the present invention. FIG. 4 is a cross-sectional view showing a modified example of the substrate holding member according to the embodiment. The substrate holding member 200 according to the present embodiment is provided with a terminal hole 142 in the electrode embedding member 100 according to the present embodiment and is provided with a terminal 140. The terminal 140 is electrically connected to the electrode 120. The terminal 140 is electrically connected to the electrode 120 includes both the terminal 140 being directly connected to the electrode 120 and the terminal 140 being connected to the electrode 120 via the connection member 130 or the like. This allows power to be supplied to the electrode 120. The terminal 140 can be formed of Ni or the like. The terminal 140 is brazed to the electrode 120 or the connection member 130 with Au solder or the like. An intermediate member 150 formed of Kovar or the like may be provided between the electrode 120 or the connection member 130 and the terminal 140.
[0042] The substrate holding member of the present invention can increase the resistance of the electrodes even with a design that does not impair the reliability of the electrodes, can increase the degree of freedom in electrode design, and can suppress the variation in the resistance value of the electrodes within the plane. Furthermore, when an electrode embedding member using a connecting member is used, the risk of a connection failure between the terminal and the connecting member can be reduced.
[0043] [Method of manufacturing electrode-embedded members] Next, a method for manufacturing an electrode-embedded member according to the present embodiment will be described. FIG. 5 is a flow chart showing a method for manufacturing an electrode-embedded member according to the present embodiment. As shown in FIG. 5, the method for manufacturing an electrode-embedded member according to the present embodiment includes a molded body forming step STEP 1, a degreasing step STEP 2, a preparation step STEP 3, a precursor forming step STEP 4, a heat treatment step STEP 5, and a firing step STEP 6. Note that the following describes a manufacturing method using a molded body hot pressing method in which molded bodies are stacked to manufacture the member, but in the present invention, it is important to C-coat the Mo electrode in the preparation step STEP 3 and the temperature and time of the heat treatment step STEP 5, and the other steps may be replaced with other methods.
[0044] 6(a) to 6(d) are cross-sectional views each showing a schematic diagram of one stage in the manufacturing process of the electrode-embedded member according to the present embodiment, in which the electrode-embedded member of FIG. 2 is manufactured.
[0045] In the molded body forming step STEP 1, a plurality of ceramic molded bodies 11, 12 are formed from ceramic raw material powder. In FIG. 6, the ceramic molded body is divided into two members, but may be three or more depending on the design. For example, additives such as binder, plasticizer, dispersant, etc. are appropriately added to the ceramic raw material powder and mixed to prepare a slurry, and granules (ceramic raw material powder) are granulated by a spray drying method or the like, and then the slurry is pressure-molded to form a plurality of ceramic molded bodies 11, 12. When a manufacturing method using a binder is used in this way, about 100 ppm to 500 ppm of C components derived from the binder remain in the ceramic degreased body even after the degreasing step described below. It is presumed that this C component also causes carbonization, but since the present invention promotes carbonization by coating the Mo mesh electrode with C, the amount of C components in the ceramic degreased body is not so important. Since the purpose of the present invention is to sufficiently carbonize Mo of the electrode, there is no problem even if such a large amount of C components remain in the degreased body. If necessary, a powder serving as a sintering aid may be added to the ceramic raw material powder.
[0046] The ceramic raw material powder is preferably of high purity, preferably 96% or more, more preferably 98% or more, and preferably has an average particle size of 0.1 μm or more and 1.0 μm or less.
[0047] The mixing method may be either wet or dry, and a mixer such as a ball mill or a vibration mill may be used. The molding method may be a known method such as uniaxial pressing or cold isostatic pressing (CIP). The method for forming the ceramic molded body is not limited to pressing, and may be, for example, green sheet lamination or casting, which may be appropriately degreased or further calcined to produce the ceramic molded body. The electrode-embedded member precursor may be formed by a powder hot pressing method.
[0048] After forming, the ceramic molded bodies 11 and 12 may be machined to adjust the shape of the molded bodies. As shown in Fig. 6(b), a recess may be formed on one side of the ceramic molded body 12 (the surface to be joined with another ceramic molded body 11) in a shape that matches the shape of the electrode 120 and the connection member 130. The recess may be provided on the ceramic molded body 11 or on both sides. The machining may be performed after degreasing.
[0049] In the degreasing step STEP 2, the ceramic molded bodies 11, 12 are degreased at a predetermined temperature or higher for a predetermined time or longer to produce a plurality of ceramic degreased bodies 21, 22. The ceramic molded bodies 11, 12 are heat treated at a temperature of, for example, 400°C or higher and 800°C or lower to become the ceramic degreased bodies 21, 22. The degreasing time is preferably 1 hour or higher and 120 hours or lower. An atmospheric furnace or a nitrogen atmosphere furnace can be used for degreasing.
[0050] In the preparation step STEP 3, an electrode 120 formed of a mesh woven with Mo wires and coated with carbon is prepared. Also, a connection member 130 is prepared as necessary.
[0051] The material of the electrode 120 is mainly composed of Mo. The term "mainly composed of Mo" means that the purity is 98 wt% or more, and the total of other transition metals, rare earth elements, or their compounds, and C is 2 wt% or less. The electrode 120 mainly composed of Mo undergoes a heat treatment step STEP 5 and a firing step STEP 6 described below, and becomes the electrode 120 composed of a bulk of Mo carbide. The electrode 120 is prepared by processing into a shape according to the design of the electrode embedding member 100. The shape is a mesh with wires woven in consideration of ease of carbonization. The wire diameter forming the mesh of the electrode 120 is preferably 0.02 mm or more and 0.15 mm or less.
[0052] The material of the connection member 130 is preferably made mainly of W. "Made mainly of W" means that the purity is 97 wt% or more, and the total of other transition metals, rare earth elements or their compounds, and C is 3 wt% or less. The connection member 130 made mainly of W is less likely to carbonize than Mo even after undergoing the heat treatment step STEP 5 and the firing step STEP 6 described below, and therefore becomes the connection member 130 containing W metal. The connection member 130 is prepared by processing into a shape according to the design of the electrode embedding member 100, and is embedded in a position according to the design.
[0053] In the precursor formation step STEP 4, the prepared electrode 120, connection member 130, and multiple ceramic degreased bodies 21, 22 are combined to form an electrode-embedded member precursor 30 formed in a flat plate shape with the electrode 120 and connection member 130 embedded therein.
[0054] In the heat treatment step STEP5, the electrode embedding member precursor 30 is heat treated at 800°C to 1500°C for 7 hours or more. As a result, the carbonization of Mo in the C-coated Mo mesh electrode 120 progresses, and the electrode embedding member precursor 30 becomes a bulk of Mo carbide. The heat treatment time may be a predetermined time according to the wire diameter of the Mo mesh electrode. For example, when the wire diameter is greater than 0.15 mm and less than or equal to 0.2 mm, the heat treatment time may be 20 hours. When the connecting member 130 mainly composed of W is used, the W in the connecting member 130 is not easily carbonized regardless of the heat treatment time, since the heat treatment is performed at a temperature relatively lower than the temperature at which W is carbonized.
[0055] In the firing step STEP6, the heat-treated electrode-embedded member precursor 30 is uniaxially pressurized and fired in a direction perpendicular to the main surface (mounting surface) to obtain the electrode-embedded member 100. The pressure is preferably 1 MPa or more. The firing temperature is preferably higher than 1500°C and lower than 2000°C. The firing time is preferably 1 hour or more and 12 hours or less. The firing atmosphere is, for example, a nitrogen or inert gas atmosphere, but may also be a vacuum atmosphere. As a result, the multiple ceramic degreased bodies 21 after the heat treatment are sintered to become ceramic sintered bodies, which are integrated to obtain the electrode-embedded member 100 in which the electrode 120 or the electrode 120 and the connection member 130 are embedded. The firing may be performed by increasing the temperature continuously from the heat treatment.
[0056] In this way, it is possible to increase the resistance of the electrode even with a design that does not impair the reliability of the electrode, thereby increasing the freedom of electrode design, and it is possible to manufacture an electrode-embedded component that can suppress variation in the resistance value of the electrode within the surface.
[0057] In addition, a ceramic calcined body preparation step may be provided between the degreasing step STEP 2 and the precursor formation step STEP 4. When the ceramic calcined body preparation step is provided, the ceramic degreased body is calcined at a temperature of 1200°C to 1700°C to prepare a ceramic calcined body. This makes it possible to improve the dimensional accuracy of the outer shape of the electrode-embedded member and the embedding positions of the electrodes and connecting members. The calcination time is preferably 0.5 hours to 12 hours. The calcination atmosphere is preferably a nitrogen or inert gas atmosphere, but may be a vacuum atmosphere. When the calcined body preparation step is provided, mechanical processing may be performed after the calcined body preparation step.
[0058] [Method of manufacturing the substrate holding member] 7(a) to 7(c) are cross-sectional views each showing a schematic diagram of a step in the manufacturing process of a substrate holding member according to the present embodiment, in which the substrate holding member of FIG. 4 is manufactured.
[0059] A terminal hole 142 is provided in the electrode-embedded member 100 after firing to expose the surface of the connection member 130. At this time, if a W carbide layer (not shown) is formed on the surface of the connection member 130, the W carbide layer in the range of the terminal hole is also removed. This allows the terminal 140 to be connected to the W metal of the connection member 130, whose resistance is kept low. The terminal 140 is connected to the exposed connection member 130 with a brazing material or the like. Ni or the like can be used for the terminal. Also, Au brazing material or the like can be used for the brazing material. An intermediate member 150 made of Kovar or the like may be disposed between the connection member 130 and the terminal 140 for brazing. When the connection member 130 is not used, the terminal 140 is brazed directly to the electrode 120 or brazed to the electrode 120 via the intermediate member 150.
[0060] In this way, it is possible to manufacture a substrate holding member 200 that can increase the resistance of the electrodes even with a design that does not impair the reliability of the electrodes, increase the degree of freedom in electrode design, and suppress the variation in the resistance value of the electrodes within the surface. Also, when an electrode embedding member using a connecting member is used, it is possible to manufacture a substrate holding member 200 that can reduce the risk of a malfunction occurring in the connection between the terminals and the connecting member.
[0061] [Examples and Comparative Examples] Example 1 Ceramic raw material powder, mainly composed of AlN with 5wt% Y2O3 added, was used for CIP molding (pressure 1ton / cm 2 ) to obtain an ingot of a molded body. This was machined to form a ceramic molded body with a diameter of 340 mm and a thickness of 5 mm, and a ceramic molded body with a diameter of 340 mm and a thickness of 30 mm. A recess with a diameter of 300 mm and a depth of 0.1 mm was provided on one side of the 30 mm thick ceramic molded body, sharing the center of the molded body, for accommodating an electrode. Furthermore, a recess with a diameter of 8.5 mm and a depth of 0.25 mm was provided at a predetermined position for forming a terminal, for accommodating a connecting member.
[0062] Next, the ceramic molded body was degreased at 550°C for 12 hours to prepare a ceramic degreased body. Next, a molybdenum mesh (wire diameter 0.1 mm, plain weave, mesh size #50) made of molybdenum with a diameter of 294 mm was cut into a specified shape. This was coated with carbon to a thickness of 1 μm by vacuum deposition to prepare an electrode. In addition, two connecting members with a size of φ8 mm x 0.2 mmt were made from W pellets. Next, the connecting members and electrodes were placed in the recesses of the ceramic degreased body with recesses, and sandwiched between the other ceramic degreased body to prepare an electrode-embedded member precursor.
[0063] Next, the electrode-embedded member precursor was placed in a hot press furnace and heat-treated for 7 hours from 800°C to 1500°C. Next, the electrode-embedded member precursor was uniaxially hot-pressed and fired at 1800°C for 2 hours while applying a force of 10 MPa in a direction perpendicular to the main surface (mounting surface) of the electrode-embedded member precursor. In this manner, the electrode-embedded member was fired.
[0064] After that, the entire surface was ground and polished to form a wafer mounting surface with a total thickness of 25 mm, an insulating layer thickness of 1.0 mm, and a surface roughness of Ra 0.4 μm. A flat-bottom hole with a hole diameter of φ5.5 mm was drilled from the back side of the ceramic base to the terminal position of the connecting member. A buffer member (intermediate member) made of Kovar with a diameter of 5 mm and a thickness of 2 mm and a cylindrical Ni power supply terminal with a diameter of 5 mm and a length of 30 mm were installed on the exposed bottom surface of the connecting member via brazing material, and brazing was performed with Au-Ni-based brazing material at 1050 ° C. in a vacuum furnace to complete the substrate holding member. In this way, the substrate holding member of Example 1 was produced.
[0065] Example 2 In Example 2, the electrodes used in Example 1 were changed to electrodes in which the wire diameter of the mesh was 0.03 mm. Otherwise, the substrate holding member of Example 2 was produced under the same conditions as Example 1.
[0066] Example 3 In Example 3, the electrodes used in Example 1 were changed to electrodes in which the wire diameter of the mesh was 0.15 mm. Otherwise, the substrate holding member of Example 3 was produced under the same conditions as Example 1.
[0067] Example 4 In Example 4, the electrode used in Example 1 was changed to a Mo mesh electrode coated with carbon to a thickness of 1 μm using a DLC (Diamond-like Carbon) coating. Otherwise, the substrate holding member of Example 4 was produced under the same conditions as Example 1.
[0068] Example 5 In Example 5, the electrode used in Example 1 was changed to a Mo mesh electrode coated with carbon to a thickness of 10 μm by carbon spraying. Otherwise, the substrate holding member of Example 5 was produced under the same conditions as Example 1.
[0069] Example 6 In Example 6, the electrode used in Example 1 was changed to an electrode in which a Mo mesh electrode was coated with graphite obtained by pyrolyzing methane gas at 2000° C. to a thickness of 10 μm. A substrate holder for Example 6 was produced under the same conditions as Example 1 except for the above.
[0070] Example 7 In Example 7, the electrodes used in Example 1 were changed to electrodes in which the wire diameter of the mesh was 0.2 mm, and the heat treatment time was changed to 20 hours. Otherwise, the substrate holding member of Example 7 was produced under the same conditions as Example 1.
[0071] Comparative Example 1 In Comparative Example 1, the electrode used in Example 1 was changed to a Mo mesh electrode not coated with carbon. Otherwise, the substrate holding member of Comparative Example 1 was produced under the same conditions as in Example 1.
[0072] Comparative Example 2 In Comparative Example 2, the electrodes used in Example 1 were changed to electrodes in which the wire diameter of the mesh was 0.2 mm, and the heat treatment time was changed to 14 hours. Otherwise, the substrate holding member of Comparative Example 2 was produced under the same conditions as in Example 1.
[0073] [Performance evaluation] (Measurement of temperature distribution) After installing the fabricated substrate holding member (heater) in the evaluation chamber, the temperature was controlled at 400°C by self-heating, and the surface distribution was measured with an IR camera. The measurement area was within a Φ290mm range, and the temperature variation was evaluated as ΔT = maximum value - minimum value.
[0074] (Evaluation of heater resistance and resistance variation) After measuring the temperature distribution, terminal holes for resistance measurement were provided at predetermined positions to expose the heater electrodes. The tester probe was brought into contact with the heater electrodes exposed in the predetermined terminal holes, and the heater resistance between the predetermined terminals was measured at eight locations (four locations on the outer periphery at a radius of 135 mm and four locations on the inner periphery at a radius of 50 mm). The ratio (Rm / Rd) of the design resistance value Rd to the measured resistance value Rm at the eight locations (maximum value - minimum value) / average value was evaluated as the resistance variation of the electrodes. In addition, the resistance value of the entire heater electrode was measured.
[0075] (Composition analysis of electrodes and connecting materials) The heater was cut in a vertical cross section passing through the center of the mounting surface and the center of the connecting member, and the cross sections of the electrodes and connecting members were exposed and polished, after which elemental analysis was performed using EMPA and qualitative analysis was performed using XRD. Elemental analysis of the electrodes was performed on three locations: the position closest to the center of the mounting surface, the position closest to the periphery, and the position closest to the midpoint of the two.
[0076] For the EPMA analysis, elemental mapping analysis of the cross section of the electrode was performed using a FE-EPMA (field emission electron probe microanalyzer), and the presence of carbides was determined using the ZAF method in terms of atom% C / (C+Mo) ratio. If the C / (C+Mo) ratio was 0.20 or higher, it was determined to be composed of Mo carbide, and if the C / (C+Mo) ratio was less than 0.20, it was determined that uncarburized Mo remained. For XRD, X-ray diffraction was performed on the cross section (a region with a diameter of approximately 3100 μm, including the diameter of the electrode) using μ-XRD (micro X-ray diffraction).
[0077] (Measurement of electrode porosity) The porosity of the electrode was measured by photographing the cross section of the electrode with a scanning electron microscope (SEM) at 1000x magnification, and binarizing a 30μm x 30μm field of view from the photographed data using free software "ImageJ" developed by the National Institutes of Health (NIH). Five fields of view were randomly selected as measurement points and observed. A porosity of 5% or less was determined to be a bulk body.
[0078] In Examples 1 to 7, Mo carbide was formed up to the center of the electrode at all three measured points by both EPMA and XRD. It was also confirmed that it was a bulk body. As a result, the variation in resistance of the heater electrode was suppressed, and the surface temperature distribution was suppressed accordingly. From the results of Examples 1 and 2, it was found that when the wire diameter was 0.1 mm or less, the electrode could be completely carbonized by heat treatment for 7 hours. On the other hand, from the results of Examples 4 and 7, it was found that when the wire diameter was 0.15 mm, heat treatment for 14 hours was required, and when it was 0.2 mm, heat treatment for 20 hours was required.
[0079] In addition, it was found from the results of Examples 1, 4, 5, and 6 that the C coating method did not affect the carbonization of the Mo mesh electrode, and that a C coating thickness of 1 μm was sufficient.
[0080] In Comparative Examples 1 and 2, the electrode closest to the center of the mounting surface had a mixed structure of Mo and Mo2C. As a result, it is believed that the resistance of the heater electrode varied, and the surface temperature distribution became larger accordingly. Comparative Example 1 was produced using the conventional manufacturing method, but due to a shortage of carbon source, the electrode was not completely carbonized and had a mixed structure of Mo and Mo2C.
[0081] In Comparative Example 2, in comparison with Example 7, it is considered that although the carbon source was sufficient, the wire diameter was large and therefore the heat treatment time was insufficient to carbonize to the center. Therefore, it was found that if the wire diameter is 0.1 mm or less, the electrode can be carbonized even with the same heat treatment time as in the past, and if the wire diameter is 0.15 mm or less, although the heat treatment time is longer than the conventional heat treatment time, the electrode can be carbonized with a heat treatment time that is commensurate with the effect, thereby suppressing the manufacturing cost.
[0082] As a result, it was confirmed that the electrodes were sufficiently carbonized in Examples 1 to 7 compared to Comparative Examples 1 and 2, and the variation in resistance of the heater electrodes was suppressed, and the surface temperature distribution was accordingly suppressed to be small. It was also confirmed that the manufacturing method of the present invention can manufacture such electrode-embedded members and substrate-holding members.
[0083] The present invention is not limited to the above-described embodiment, and it goes without saying that various modifications and equivalents are included within the spirit and scope of the present invention. In addition, the structure, shape, number, position, size, etc. of the components shown in each drawing are for convenience of explanation and may be changed as appropriate. [Explanation of symbols]
[0084] 11, 12 Ceramic molding 21, 22 Ceramic degreased body 30 Electrode embedding material precursor 100 Electrode embedding member 110 Base 112 Placement surface 120 electrodes 130 Connection member 140 Terminals 142 Terminal hole 150 Intermediate parts 200 Substrate holding member
Claims
1. An electrode embedding member, A flat plate-shaped base body made of a ceramic sintered body; an electrode formed of a mesh of woven wires and embedded in the substrate; The electrode is made of a bulk of Mo carbide, A connection member including a W metal electrically connected to the electrode and embedded in the base body is further provided, The connection member has a W carbide layer on a surface thereof.
2. An electrode embedding member as described in claim 1, characterized in that the wire diameter of the wire forming the mesh of the electrode is 0.02 mm or more and 0.15 mm or less.
3. An electrode embedding member according to claim 1 or claim 2, and a terminal electrically connected to the electrode.
4. A method for manufacturing an electrode-embedded member formed of a ceramic sintered body, comprising the steps of: a compact forming step of forming a plurality of ceramic compacts from the ceramic raw material powder; a degreasing step of degreasing the plurality of ceramic molded bodies at a predetermined temperature or higher for a predetermined time or longer to produce a plurality of ceramic degreased bodies; A preparation step of preparing an electrode formed of a mesh of woven Mo wires and coated with carbon; The electrode and the plurality of ceramic degreased bodies are combined to form a flat plate, a precursor forming step of forming an electrode-embedded member precursor having an electrode embedded therein; a heat treatment step of heat treating the electrode-embedded member precursor at 800° C. or more and 1500° C. or less for 7 hours or more; a firing step of uniaxially pressurizing and firing the heat-treated electrode-embedded member precursor in a direction perpendicular to a main surface of the electrode-embedded member precursor to obtain an electrode-embedded member.
Citation Information
Patent Citations
Silicon nitride member and its manufacture
JP1992087181A
Ceramics heater
JP1995135068A
Manufacture of ceramic heater
JP2000012194A
Semiconductor manufacturing and inspecting device
JP2001332560A
Ceramic chuck
JP2005175179A